PENGEMBANGAN HANDOUT BERGAMBAR DISERTAI PETA KONSEP PADA MATERI SISTEM PENCERNAAN UNTUK SISWA SMP - Octavia, Hayuni; Sumarmin, Ramadhan; Sari, Liza Yulia (Pendidikan Biologi, 2013)
ABSTRACT learning process can be done well if the interaction between teachers and students. Moreover, learning is also supported by appropriate learning media. teachers should use the media within their learning needs students who are taught. As for one of the materials that can be in use as an aid students in understanding the biology of learning material sytem digestion is illustrated handout that accompanied the map concept. based on this, has done research on the development of pictorial handout material with a concept map on the digestive system for junior high school students are valid and practical. This type of research is the development of research, using 4D models that consist of four hapan ie, defaine, design, develop, and dessiminate. however, in this study, stage dessiminete not done. handout developed validated by the validator and the practicalities of four topical done one teacher and class VIII SMP 10Solok Selatan. Data in this study were primary data obtained from questionnaires validity assessment and practicalities. Data were analyzed using analysis describtive. of this study produced a product in the form of a pictorial handout material with a concept map on the digestive system for junior high school students. handout produced has an average value of86.98%  with  the  criterion  validity valid,  while  average  scores  by teachers  practicalities93.05% and 92.80% of students with very practical criteria. it can be concluded that the pictorial handout material with a concept map on the digestive system for junior high school students valid and very practical.